(untitled) (PJDOL, 2023)
Peaceful coexistence for a stable and progressing world demands the creation of a culture of peace which may be developed by teaching certain peace values. This study examines the presence of peace values in the textbooks of compulsory subjects (English, Urdu, Islamic Studies andPakistan Studies) for secondary school students (i.e.